1979
DOI: 10.1073/pnas.76.2.561
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational interaction of hadrons and leptons: Linear (multiplicity-free) bandor and nonlinear spinor unitary irreducible representations of S̄L̄ (4 R )

Abstract: We review two possible affine extensions of gravity connected to the strong interactions. In the metric affine theory, torsion and nonmetricity do not propagate, gravitation is effectively unmodified, and the observed approximate conservation of hadron intrinsic hypermomentum—i.e., scaling, SU (6), and Regge trajectories—is due to the ḠL̄ (4, R ) band-spinor structure of the hadrons. In the second approach, the new gravitational Lagrangian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Note that in this model the connection is non-Lorentzian and the non-metricity 1-form (represented by Q) is non-vanishing. The bosonic sector of metric-affine gravity was analyzed, for instance, in References [62][63][64][65], while the fermionic part is more delicate (see for instance References [66][67][68][69]). In this respect, there is no finite dimensional spinor representation of the GL(4, ) group, which leads to the introduction of the "world spinors" (with infinite components) of Ne'eman, and to the corresponding generalization of Dirac equation.…”
Section: Quadratic Gauge Gravity Models In Metric-affine Gravitymentioning
confidence: 99%
“…Note that in this model the connection is non-Lorentzian and the non-metricity 1-form (represented by Q) is non-vanishing. The bosonic sector of metric-affine gravity was analyzed, for instance, in References [62][63][64][65], while the fermionic part is more delicate (see for instance References [66][67][68][69]). In this respect, there is no finite dimensional spinor representation of the GL(4, ) group, which leads to the introduction of the "world spinors" (with infinite components) of Ne'eman, and to the corresponding generalization of Dirac equation.…”
Section: Quadratic Gauge Gravity Models In Metric-affine Gravitymentioning
confidence: 99%
“…So there are widespread usage areas for affine symmetry from particle physics to gravitation [10,12,14,23,[54][55][56][57]. For instance, according to the papers [10][11][12][13][14][15], the gauge theory of affine group could play an important role for solving the renormalizability or unitarity problems on quantum gravity by means of the general linear connection which contains additional degrees of freedom. Also, the paper [58] demonstrated that the pure affine field theory developed by Einstein [59] and Schrödinger [60], known as the Einstein-Schrödinger theory, provides the unification of quantum theory and Einstein's general theory of relativity and this theory can be quantized by the rules of canonical quantization, but the author says that this quantization is physically meaningless.…”
Section: Discussionmentioning
confidence: 99%
“…Another study, named as the metric-affine gauge theory of gravity (MAG), generalized the Poincaré gauge theory of gravity with non-vanishing nonmetricity tensor [9,10]. Later on, the papers [11][12][13][14][15] suggested that the renormalizability and unitarity problems in quantum gravity can be solved by taking the affine group as the dynamical group in a gauge theory of gravity by the help of general linear connection Γ α µν [10]. There is an interesting study which is based on GL(4, R) gauge theory of gravity, proposes a unified theory between the electromagnetic and gravitation fields in the concept of purely affine formulation of the Einstein-Maxwell theory [16].…”
Section: Introductionmentioning
confidence: 99%